2011
DOI: 10.1016/j.neuropsychologia.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Areas of left perisylvian cortex mediate auditory–verbal short-term memory

Abstract: A contentious issue in memory research is whether verbal short-term memory (STM) depends on a neural system specifically dedicated to the temporary maintenance of information, or instead relies on the same brain areas subserving the comprehension and production of language. In this study, we examined a large sample of adults with acquired brain lesions to identify the critical neural substrates underlying verbal STM and the relationship between verbal STM and language processing abilities. We found that patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…A verbal memory test (BCcog-SRT) was found to be correlated logically to regions of importance for episodic memory (thalamus, fornix, hippocampus, frontal lobe) and for recognizing words (lingual gyrus) [ 46 ]. Digit span was found to be correlated with perisylvian atrophy, as previously described [ 47 ]. DSST, a speed writing test, was found to be correlated with the precentral gyrus, which is also the primary motor cortex, indispensable to do this test.…”
Section: Neural Basis Of Cognitive Impairment In Nmosupporting
confidence: 69%
“…A verbal memory test (BCcog-SRT) was found to be correlated logically to regions of importance for episodic memory (thalamus, fornix, hippocampus, frontal lobe) and for recognizing words (lingual gyrus) [ 46 ]. Digit span was found to be correlated with perisylvian atrophy, as previously described [ 47 ]. DSST, a speed writing test, was found to be correlated with the precentral gyrus, which is also the primary motor cortex, indispensable to do this test.…”
Section: Neural Basis Of Cognitive Impairment In Nmosupporting
confidence: 69%
“…Superior temporal cortices are now routinely implicated in functional neuroimaging studies of auditory short-term memory (e.g., Buchsbaum et al, 2005;Strand, Forssberg, Klingberg, & Norrelgen, 2008), and anatomical neuroimaging studies have found correlations between the macroanatomical structure of the superior temporal cortex and verbal working memory capacity in individuals with both language-impaired and developmentally typical profiles (Lu et al, 2016;Richardson et al, 2011). These results parallel growing evidence from large-sample studies of auditory short-term memory deficits following brain injury, which specifically attribute this impairment to lesioned tissue in left superior temporal cortex (Koenigs et al, 2011;Leff et al, 2009). Transcranial magnetic stimulation (TMS) applied to left posterior superior temporal gyrus (STG) has also been shown to interfere in the maintenance of nonwords in short-term memory (Acheson, Hamidi, Binder, & Postle, 2011).…”
mentioning
confidence: 56%
“…TMS studies of phonological working memory have shown that disruption of the posterior superior temporal region in the left hemisphere disrupts phonological working memory as well as language production ; however, corresponding sites in the right hemisphere were not assessed. Lesion studies, on the other hand, have overwhelmingly demonstrated that phonological working memory deficits are associated with specifically left hemisphere injury (e.g., Koenigs et al, 2011;Leff et al, 2009). Structural neuroimaging studies have also found relationships between superior temporal morphometry of the left, but not right, hemisphere and phonological working memory ability (Richardson et al, 2011).…”
Section: Phonological Working Memory Beyond Left Stgmentioning
confidence: 99%
“…Instead, the increased excitability elicited by anodal tDCS (during stimulation; Stagg & Nitsche, 2011) facilitated the acquisition of the phonological forms of the nonwords in long-term memory. This effect is likely to reflect the contributions of a number of neighbouring brain regions supporting aspects of phonological processing, including phonological short-term memory (Warrington & Shallice, 1969;Paulesu, Frith, & Frackowiak, 1993;Jonides et al, 1998;Henson, Burgess, & Frith, 2000;Buchsbaum & Esposito, 2008;Buchsbaum, Padmanabhan, & Berman, 2010;Acheson et al, 2011;Koenigs et al, 2011), phoneme sequencing (Gelfand & Bookheimer, 2003;Moser et al, 2009), translation of auditory to articulatory representations (Hickok & Poeppel, 2000;Papoutsi et al, 2009;Hickok, Houde, & Rong, 2011;Peschke, Ziegler, Eisenberger, & Baumgaertner, 2012), stimulus-driven attention (Downar, Crawley, Mikulis, & Davis, 2001;Ravizza, Hazeltine, Ruiz, & Zhu, 2011;Cabeza, Ciaramelli, & Moscovitch, 2012) and auditory processing for speech (posterior superior temporal cortex).…”
mentioning
confidence: 99%